Analysis of Fibre Quality in a Gossypium Hirsutum Ã— G. Barbadense Backcross Introgression Population - PALVE, S. M.; MANDHYAN, P. K.; WAGHMARE, V. N.; KATE, N. (Cotton Research Journal, 2021)
Attempts to introgress genes from G. barbadense into upland cotton have resulted in achieving stable introgression of fibre quality traits and disease resistance in the background of upland cotton. For the present study, F1 generatedcrossing Suraj (G. hirsutum) as the recipient parent and Suvin (G. barbadense) as the donor parent in 2013. The F1(Suraj Ã— Suvin) was backcrossed to Suraj to produce BC1F1 population during 2014. In 2018 data was collected on 19 BC1F4 progeniesfor fibre quality traits i. e. Nep (count/g), SCn (count/g), L (w) mm, L (n) mm and SFC (n) using Advanced Fibre Information Sysem (AFIS) with the objective of selecting lines with least negatively related traits values for further use in cotton breeding. Five BC1F4 progenies namely, SPS36-94, SPS37-94, SPS41-94, SPS46-31and SPS 49-31 were identified as promising for all the fibre quality traits combining lower mean values of nep (cnt/g), seed coat nep (cnt/g) short fibre content by number (%<12.7mm) and higher values of length by weight (mm), length by number (mm) and upper quartile length by weight (mm).The results of present studyindicate that release of abundant genetic variation or fibre quality traits in the BC1F4 progenies produced by backcrossing and continuous self-pollination.